Implementasi Multi-Agent Path Finding Menggunakan Algoritma Conflict-Based Search Pada Game Bergenre Adventure-Puzzle - Fathony Teguh Irawan; Eriq Muh. Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Artificial intelligence usage in video games is not new thing anymore. In general, most of video games now take advantage of artificial intelligence on entities in their video games. The problem that occurs is the impact of the implementation of artificial intelligence on the performance of video game. Multi-agent pathfinding is there to try to find path for the agents registered. Multi-agent pathfinding has some constraint that doesn't let more than one agent occupying same place at the same time. In this study, researcher propose to use conflict-based search algorithm to solve multi-agent pathfinding constraint. The design of multi-agent pathfinding is by designing conflict-based search for high-level search and A* search for low-level search. Implementation of multi-agent pathfinding is based on the design that has been defined, implemented on Unity3D game engine using C# programming language. Testing process is conducted after the implementation is completed and found the result is there is no condition where more than one agent occupy same place at the same time. Resource usage of conflict-based search also shown to be at stable rate. FPS that obtained from multi-agent pathfinding is still considered as playable. However, cycle time that generated while running conflict-based search continuous to growth as the number of agents increases. With this implementation is expected to help game developer to implement multi-agent pathfinding in their video game.